A Simple Econometric Model for the United States, 1947-1950 - Fisher, Gene H. (The Review of Economics and Statistics, 1952)
IN recent years several attempts have beeni made to set up macro-econometric models for the United States and to derive statistical estimates of relevant parameters for the prewar period.1 To the knowledge of the present author few, if any, attempts have been made to deal statistically with econometric models using postwar data. There are good reasons for this. In the first place if annual data are used, too few observations will be available for an adequate statistical analysis. If monthly or quarterly data are utilized, then difficult problems arise, for example the treatment of seasonal variation and the possibility of substantial correlation of disturbances. In spite of these latter difficulties an attempt is made in the present paper to analyze statistically a very simple econometric model for the United States using quarterly national income data for the period I947-50. The statistical analysis is admittedly weak at certain points and must therefore be regarded as preliminary and tentative. In addition to the difficulties mentioned above the problem of multicollinearity 2 is present, as is usually the case in multiple correlation studies involving economnic data. All of this means, of course. that the regression coefficients tend to be rather uncertain and that therefore the estimates of the structural parameters must be interpreted with caution.